2019
DOI: 10.1073/pnas.1812066116
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and host immune evasion in Staphylococcus aureus mediated by a metabolic adaptation

Abstract: Staphylococcus aureus is a notorious human bacterial pathogen with considerable capacity to develop antibiotic resistance. We have observed that human infections caused by highly drug-resistant S. aureus are more prolonged, complicated, and difficult to eradicate. Here we describe a metabolic adaptation strategy used by clinical S. aureus strains that leads to resistance to the last-line antibiotic, daptomycin, and simultaneously affects host innate immunity. This response was characterized by a change in anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 44 publications
4
88
0
Order By: Relevance
“…Daptomycin was found to attract and cluster fluid lipids in the membrane, causing membrane depolarization and delocalization of membrane proteins (41). Jiang et al found some clinical daptomycin-resistant mutants had gain-of-function mutations in cls 2, leading to increased CL content and decreased PG content, which then resulted in decreased daptomycin susceptibility (42). Zhang et al have found that CL renders liposomes impermeable to daptomycin and proposed that this could be due to the prevention of flipping of the daptomycin to the inner leaflet of liposomes (43).…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin was found to attract and cluster fluid lipids in the membrane, causing membrane depolarization and delocalization of membrane proteins (41). Jiang et al found some clinical daptomycin-resistant mutants had gain-of-function mutations in cls 2, leading to increased CL content and decreased PG content, which then resulted in decreased daptomycin susceptibility (42). Zhang et al have found that CL renders liposomes impermeable to daptomycin and proposed that this could be due to the prevention of flipping of the daptomycin to the inner leaflet of liposomes (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about how modification of cell membrane biochemistry affects resistance. Changes in membrane phospholipid composition was recently shown to increase Staphylococcus aureus resistance to daptomycin (41), and changes in LPS biosynthesis in E. coli increased sensitivity to bacitracin and rifampicin (30). Our work adds to the evidence that resistance can repeatedly evolve through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 55%
“…While not directly conferring DAP resistance, it is clear that cls mutations play an important role in the enterococcal counterattack against DAP. The prevalence of these mutations in the clinic, across species (56), across adaptive environment, and across DAP resistance mechanisms suggests that these alleles may act as good diagnostic DAP resistance markers in clinical infections.…”
Section: Discussionmentioning
confidence: 99%